The Relationship between Service Quality and Patient Safety Goals in the Inpatient Ward of UPTD RSUD Datu Beru Aceh - Andini Mentari Tarigan; Chairulsyah Putra; Wira Helmanita; Rudi Purwana (LLDIKTI Wilayah 1, 2023)
The patient safety goals are accurate patient identification, improved effective communication, improved safety of high-alert medications, ensuring correct site, procedure, and patient surgery, reducing the risk of healthcare-associated infections, and reducing the risk of patient falls. This study aimed to determine the relationship between service quality and patient safety goals in the inpatient ward of UPTD RSUD Datu Beru Aceh. The research method used in this study was a quantitative method with a cross-sectional approach. The study was conducted at UPTD RSUD Datu Beru Aceh from January to September. The study population consisted of 370 inpatient nurses. Purposive sampling technique was used to collect samples using the Slovin formula with a total of 79 respondents. The results of the study showed that there was a relationship between responsiveness with a p-value of 0.000 < 0.05, assurance with a p-value of 0.000 < 0.05, reliability with a p-value of 0.000 < 0.05, empathy with a p-value of 0.000 < 0.05, and tangibles with a p-value of 0.001 < 0.005 towards patient safety in the inpatient ward of Datu Beru Aceh Regional Hospital. In conclusion, there is a relationship between responsiveness, assurance, reliability, empathy, and tangibles with patient safety in the inpatient ward of Datu Beru Aceh Regional Hospital. The hospital is recommended to maintain the quality of service and patient safety in the inpatient ward of Datu Beru Aceh Regional Hospital. The conclusion of the study is that there is a relationship between responsiveness, assurance, reliability, empathy, and tangibility with patient safety in the inpatient ward of UPTD RSUD Datu Beru Aceh. It is recommended that the hospital maintains the quality of services and patient safety at UPTD RSUD Datu Beru Aceh.